Enhanced chondrogenesis differentiation of human induced pluripotent stem cells by MicroRNA-140 and transforming growth factor beta 3 (TGFβ3). (March 2018) - Mahboudi, Hossein; Soleimani, Masoud; Enderami, Seyed Ehsan; Kehtari, Mousa; Ardeshirylajimi, Abdolreza; Eftekhary, Mohamad; Kazemi, Bahram
Abstract: Induced pluripotent stem cells (iPSCs) make an attractive source for regenerative medicine. The objective of our study was to establish a new method for differentiation of human iPSCs toward chondrocyte by overexpression of MicroRNA-140 (miR-140) and use of transforming growth factor beta 3 (TGFβ3) in high-cell density culture systems. We prepared vectors and then was used for recombinant Lenti virus production in HEK-293 cell. Transducted cells were selected and cultured in pellet culture system and were harvested after days 7, 14 and 21. Real-time PCR was performed to evaluate the cartilage-specific genes in the mRNA levels. Also, in order to confirm our results, we have done immunological assay. iPSCs were transducted with recombinant Lenti virus and miR-140 was expressed. Immunological methods confirmed that differentiation of iPSC toward chondrocyte with handling cartilage matrix genes. Also real time PCR demonstrated that in transducted iPSCs significantly increased gene expression of collagen type II, SOX9 and aggrecan, and down-regulated expression of collagen type I when compared to the mRNA levels measured in non transducted iPSCs. In Conclusion, our data implies that miR-140 is a potent chondrogenic differentiation inducer for iPSCs and also, we have showed increasing chondrogenic differentiation by using overexpression of miR-140 and TGFβ3.